DISCRETE FLOW ON UNIFORM STRUCTURE OF SET F(T,X) - Dervishi, Neki (Matematichki Bilten, 2009)
In this paper is proved that, if \(T\) is a discrete topological abelian group, and if \(X\) is a Hausdorff uniform space, then the mapping \(μ(f,t)=f_t\), defines a general discrete flow on uniform structure of the set \(F(T,X)\) related to the relative uniformity of pointwise convergence.